The Effect of Live Selling and Price Promotion Strategies on Purchase Intention Through Impulsive Buying Tendency on Tiktok Live Streaming: A Study of Millennials in Gorontalo - Michael Samuel Tupamahu; Nuri Wulandari; Enny Haryanti; Whony Rofianto (Jurnal Inovasi Global, 2026)
The growth of live-streaming-based e-commerce in Indonesia, especially through the TikTok Live feature, underscores the need to understand the psychological mechanisms that mediate the influence of digital marketing strategies on the purchase intention of millennial consumers in non-metropolitan areas such as Gorontalo Province. This study aims to analyze the influence of live selling and price promotion strategies on purchase intention, either directly or through impulsive buying tendency as a mediating variable among the millennial generation of TikTok Live users in Gorontalo. The study employed a quantitative approach using the Stimulus–Organism–Response (SOR) framework and involved 150 millennial respondents who had witnessed or made purchases through TikTok Live. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS. The results of the study indicate that live selling and price promotion strategies have a positive and significant effect on impulsive buying tendency, and impulsive buying tendency, in turn, has a positive and significant effect on purchase intention. Furthermore, impulsive buying tendency was found to significantly mediate the influence of live selling strategies and price promotion on purchase intention. These findings confirm that impulsivity serves as a key psychological mechanism in converting digital marketing stimuli into purchase intention among millennial consumers in non-metropolitan areas. The results also demonstrate that the effectiveness of TikTok Live strategies is not solely determined by price promotions but also by the quality of live selling interactions and the proportionate management of emotional stimuli.